2012
DOI: 10.1158/1055-9965.epi-12-0495
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the HOXB13 G84E Germline Mutation in Familial Prostate Cancer

Abstract: Background A recent study of familial and early onset prostate cancer reported a recurrent rare germline mutation of HOXB13 among men of European descent. The gene resides within the 17q21 hereditary prostate cancer linkage interval. Methods We evaluated the G84E germline mutation (rs138213197) of HOXB13 in a case-control study of familial prostate cancer at Vanderbilt University to independently evaluate the association of the mutation with familial prostate cancer. We genotyped 928 familial prostate cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 35 publications
8
75
1
1
Order By: Relevance
“…Recently, a variant in the HOXB13 gene was identified as the first germline mutation consistently and specifically associated with familial PrCa in men of European ancestry [1]. The increased PrCa risk conferred by the p.(Gly84Glu) mutation, also described as G84E, has been confirmed by several other authors [2][3][4][5][6] and it is now believed that this variant is a founder mutation originated in Scandinavia [4][5][6]. Subsequent studies have identified other HOXB13 variants in PrCa patients of African and Asian descent [1,2,7] and we have recently performed the first systematic full gene analysis of HOXB13 in early-onset and/or familial PrCa patients of Southern European origin [8].…”
Section: Introductionmentioning
confidence: 82%
“…Recently, a variant in the HOXB13 gene was identified as the first germline mutation consistently and specifically associated with familial PrCa in men of European ancestry [1]. The increased PrCa risk conferred by the p.(Gly84Glu) mutation, also described as G84E, has been confirmed by several other authors [2][3][4][5][6] and it is now believed that this variant is a founder mutation originated in Scandinavia [4][5][6]. Subsequent studies have identified other HOXB13 variants in PrCa patients of African and Asian descent [1,2,7] and we have recently performed the first systematic full gene analysis of HOXB13 in early-onset and/or familial PrCa patients of Southern European origin [8].…”
Section: Introductionmentioning
confidence: 82%
“…The variant was subsequently shown to be associated with both hereditary and sporadic prostate cancer in many independent study populations. 6370 Continued focus on early onset prostate cancer cases may provide an opportunity to identify novel genetic loci associated with increased risk for this disease.…”
Section: Genetic Focus In Early Onset Prostate Cancermentioning
confidence: 99%
“…These investigators genotyped 930 controls without a personal or family history of PC and 928 familial cases, and observed the mutation in 16 of the familial cases versus only two controls (OR =7.9, 95% CI =1.8–34.5). The carrier rate was 1.9% in all probands, but it went up 30% in cases who had ≥3 affected family members 45. The primary result was also confirmed in the much larger International Consortium for Prostate Cancer Genetics study in which investigators genotyped the G84E variant and 14 other single-nucleotide polymorphisms (SNPs) in 2,443 families 46.…”
Section: Hoxb13 Findings Replicatedmentioning
confidence: 77%